2021
DOI: 10.3390/cells10092469
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effect of Anatomical Site on Multiple Differentiation of Adipose-Derived Stem Cells in Rats

Abstract: Mesenchymal stem cells (MSCs) derived from adipose tissue are evolved into various cell-based regenerative approaches. Adipose-derived stem cells (ASCs) isolated from rats are commonly used in tissue engineering studies. Still, there is a gap in knowledge about how the harvest locations influence and guide cell differentiation. This study aims to investigate how the harvesting site affects stem-cell-specific surface markers expression, pluripotency, and differentiation potential of ASCs in female Sprague Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…In this study, we found that third-passage cells from diverse sites did not express any of these three genes. These findings are in line with [ 30 , 40 ] and consistent with another study [ 39 ] on adult human MSCs that declared that only Nanog was expressed. On the contrary, Castella et al [ 41 ] reported the expression of these three genes in r-AdMSCs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we found that third-passage cells from diverse sites did not express any of these three genes. These findings are in line with [ 30 , 40 ] and consistent with another study [ 39 ] on adult human MSCs that declared that only Nanog was expressed. On the contrary, Castella et al [ 41 ] reported the expression of these three genes in r-AdMSCs.…”
Section: Discussionsupporting
confidence: 93%
“…For PCR amplification, the resultant cDNA was utilized. PCR cycling was accomplished in a Veriti Thermal Cycler (Thermo Fisher Scientific, Waltham, MA, USA) according to [ 30 ]. All examinations were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Tang et al, 55 human S‐WAT ADSCs showed better chondrogenic potential and immunosuppression than V‐WAT ADSCs (V‐ADSCs) in vitro, although the proliferation of V‐ADSCs was significantly greater. Hendawy et al 61 analysed the ADSCs from different visceral adipose tissue depots of rats, suggesting that the mesenteric ADSCs showed a better chondrogenic differentiation potential than peri‐ovarian and peri‐renal ADSCs.…”
Section: Adscs As the Seed Cellsmentioning
confidence: 99%
“…The phenotypic characteristics of MSC from different tissues were not homogenous [ 18 ]. Its differentiation potential and proliferation rate depends on the anatomical localization [ 19 ], isolation procedures [ 20 ], and donor age [ 21 ]. Although MSC can be easily expanded in vitro, their proliferative capacity is limited because they senesce after several rounds of proliferation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%